Estudo sobre a dinâmica de organização do "si mesmo" de adolescentes do sexo feminino em conflito com a lei - Coelho, João Paulo Lopes (2013)
This research forms a study about the self organization dynamics of female people to accomplish socioeducational measures liberty deprivation. This investigation is focused on culture of stigmatization impacts and daily violence (still, strongly, present in youth detention) on these teenage subjectivation processes. It intents to analyse the way how teenagers of Centro Educacional Aldaci Barbosa Mota organize a self-concept, tangled in structuring constraints ,that features the specific types of discoursive interactions of the only Ceará feminine exclusive unity designed to accomplish restrictive and privative social-educational measures. This dissertation content is divide in three analyses block, which reference to essential elements when it comes to a cultural-historical approach of the self: a) the instruments-signs, which enable the institucional discourses and practices mapping of the unity that teenagers are part of; b) the discoursive interaction about the "self", which enable the analyses of the way female young people use cultural tools talking about themselves; c) the self-organization process, which enable to enlighten the intramental negotiation processes between positioning e personal e collectives "voices" that constraint the development of the sense of self. The research corpus consisted of a field journal constructed from Participant Observation and video recordings of activities proposed in a Thematic Workshop. The criteria for the workshop participation were: invitation’s free acceptance; establishing of socio-educational measures; and being labeled as "undisciplined". Eight teenagers participated. The material produced during the workshop was put into a Microgenetic Analysis approach. As main results, it is emphasized that: models repressor-correctional and educational-corrective service point to a socio-educational reality in which acts of violence and disciplinary practices combine a corrective logic that legitimizes the routine violation of adolescents rights; violence and stigmatization features of this unit are strongly related to the female gender issue; the diversity of meanings’ reduction in moral systems evidenced in the ways of talking about the "self" so markedly abided. We can conclude that the nature of correctional service acts on the reification of "himself", instead of facilitating the construction of meanings and senses, it could can really help those teenagers in the reconstruction process of the sense of themselves.